Comparison of mulligan technique versus muscle energy technique in patients with adhesive capsulitis - Khalil, Rabia; Tanveer, Fahad; Asif Hanif; Ahmad, Ashfaq (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the effects of Mulligan technique and muscle energy technique in patients with adhesive capsulitis. Methods: The randomised controlled trial was conducted at the Department of Physiotherapy, Government Mian Munshi Hospital, Lahore, Pakistan, from September 1, 2019, to March 31, 2020, and comprised patients with adhesive capsulitis who were randomised into Mulligan mobilisation Group A and muscle energy technique Group B. The outcome assessor was kept blinded to the treatment plan. Pain, range of motion and functional disability were measured using Visual Analogue Scale, universal goniometer and Shoulder Pain and Disability Indexat baseline, and subsequently at the end of third and sixth weeks. Data was analysed using SPSS 24. Results: Of the 78 subjects, 39(50%) were in each of the two groups. Group A had 11(28%) male and 28(72%) female patients, while Group B had 20(51%) male and 19(49%) female patients. Both groups showed significant improvement (p<0.001), and inter-group comparison showed the difference to be non-significant at baseline and third week (p>0.05).However, post-intervention difference showed significantly better results in Group A compared to Group B (p<0.05). Conclusion: Mulligan technique was found to be more effective than muscle energy technique in improving range of motion, and in reducing pain and functional disability. Clinical Trial Number: IRCT 20200605047660. https://www.cochranelibrary.com/es/central/doi/10.1002/central/CN-02171904/full Key Words: Adhesive capsulitis, Mulligan technique, Muscle energy technique.